Technology in Black Feminist World. - Hall, K. Melchor Quick (Frontiers: A Journal of Women Studies, 2019)
The article focuses on personal account of the author's experience of studying graduate-level computer science as a woman of color. It mentions challenging intersections of race, American nationalism, technology, and the university classroom and energetically imagines how futuristic technology may function positively in a black feminist world. It also mentions culture technologies rooted in the African American experience and revolutionize human-computer interaction.